Spreading patterns diffusional change in the English system of complementation - Smet, Hendrik De. (New York ; Oxford : Oxford University Press, 2013)
This volume examines the emergence and spread of three types of complements from the Middle English period to the present day.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Grammar, Comparative and general -- Complement; Grammar, Comparative and general -- Verb phrase; Linguistic change; English language -- Grammar, Historical; English language -- History